2022
DOI: 10.1021/acs.jmedchem.2c00076
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationships of 8-Hydroxyquinoline-Derived Mannich Bases with Tertiary Amines Targeting Multidrug-Resistant Cancer

Abstract: A recently proposed strategy to overcome multidrug resistance (MDR) in cancer is to target the collateral sensitivity of otherwise resistant cells. We designed a library of 120 compounds to explore the chemical space around previously identified 8-hydroxyquinoline-derived Mannich bases with robust MDR-selective toxicity. We included compounds to study the effect of halogen and alkoxymethyl substitutions in R5 in combination with different Mannich bases in R7, a shift of the Mannich base from R7 to R5, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…Previously, we have reported 8-hydroxyquinoline derived Mannich bases possessing excellent water solubility related to their zwitterionic form [12,13]. Additionally, the CH 2 -N subunit at the seventh position on the HQ ring proved to be beneficial in terms of MDR selectivity [5,7]. We have shown that the cytotoxicity and MDR-selectivity of 8-hydroxyquinoline Mannich bases are related to their complex formation with essential metal ions [5,7,14].…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…Previously, we have reported 8-hydroxyquinoline derived Mannich bases possessing excellent water solubility related to their zwitterionic form [12,13]. Additionally, the CH 2 -N subunit at the seventh position on the HQ ring proved to be beneficial in terms of MDR selectivity [5,7]. We have shown that the cytotoxicity and MDR-selectivity of 8-hydroxyquinoline Mannich bases are related to their complex formation with essential metal ions [5,7,14].…”
Section: Introductionmentioning
confidence: 88%
“…A recently proposed strategy to overcome multidrug resistance is to target the collateral sensitivity of otherwise resistant cells by MDR-selective compounds. In earlier work, we designed a library containing a high number (>500) of 8-hydroxyquinoline (HQ) derivatives possessing variable MDR-selective toxicity [5][6][7]. The toxicity of MDR-selective 8-HQ derivatives is increased, rather than decreased, by P-gp [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Introduction of selenium into organic molecules has recently been the subject of intense research as organoselenium compounds have found widespread applications in the field of drug discovery . Quinoline-containing organoselenium compounds have recently received considerable attention because the quinoline moiety is a well-documented privileged structure in natural products and pharmaceuticals for discovering lead compounds. Among the numerous selenyl-substituted quinoline derivatives, 3-selenoacetyl quinolines are an important class of compounds; much effort has been devoted to the preparation of this compound.…”
mentioning
confidence: 99%